Global Wildfire Database for GWIS (2021) - Tomàs Artés Vivancos (PANGAEA, 2022)
Global Wildfire Database for GWIS (2021) is an individual fire event focused database. Post processing of MCD64A1 providing geometries of final fire perimeters including initial and final date and the corresponding daily active areas for each fire. This dataset is an update of the data related with GlobFire (https://doi.org/10.6084/m9.figshare.10284101). Global fire monitoring systems are crucial to study fire behaviour, fire regimes and their impact at the global scale. Although global fire products based on the use of Earth Observation satellites exist, most remote sensing products only partially cover the requirements for these analyses. These data do not provide information like fire size, fire spread speed, how fires may evolve and joint into single event, or the number of fire events for a given area. This high level of abstraction is very valuable; it makes it possible to characterize fires by types (either size, spread, behaviour, etc.). Here, we present and test a data mining work flow to create a global database of single fires that allows for the characterization of fire types and fire regimes worldwide. This work describes the data produced by a data mining process using MODIS burnt area product Collection 6.1 (MCD64A1). The entire product has been computed until the present and is available under the umbrella of the Global Wildfire Information System (GWIS). For this release using MCD64A1 C6.1 HEG has been replaced by GDAL for reprojection and polygonizing process.